Dialectics Between Religion and Culture (Sculptor ’S Reception Towards the Hadith About Carving Statue in Prumpung Magelang) - Ahmad Mustofa (Analisa: Journal of Social Science and Religion, 2020)
Islam as a doctrine has a unique relationship with culture. The uniqueness was emerging when Islam as a doctrine has to confront a tradition living in a community. This study discusses how the sculptors in Prumpung Magelang negotiate and compromise betwen the two of opposite entities in the comunity, that is (1) religious doctrines (sourced from authoritative texts) about the prohibition of crafting the image of living being, and (2) cultural and artistic practices of making living being as perfect objects of artistic passion. This research attempts to explore and understand the creative reasoning model of some sculptors in the area of Prumpung Magelang when they have to appreciate their artistic passion in sculpture without having to confront the meaning of authoritative texts. Through a reception theory approach, this research concluded that the compromise and negoitation of two opposite entities which often creates polemics in the community can be accommodated in a work of art with objects of living things but still within the corridors and boundaries allowed by the text authority (hadith).